BUILDING LEADERSHIP IN NURSING PRACTICE - Ceranic, Jelica; Pelicic, Damir; Saveljic, Mitar (Sanamed, 2024)
In the pursuit of a competent and competitive healthcare system, nurses and healthcare technicians, as key figures in the healthcare process and scientific discipline of nursing, should possess not only professional knowledge but also managerial abilities and skills. This includes the effective management of human and material resources within the healthcare system. Leadership in nursing practice can be understood as the influence of head nurses on the quality and effectiveness of all activities within their domain. By reviewing the literature on research concerning leadership in nursing and the factors influencing its development in nursing practice, which have not yet been definitively defined, we aim to provide an overview for the professional community in the fields of biomedicine and health, especially in healthcare where nurses operate at all levels. To achieve the goals necessary for developing leadership in nursing practice, the implementation of appropriate strategies, methods, and tools within the healthcare system is crucial for human resources, a key factor in improving healthcare delivery. The role of the head nurse, or nursing leader, is of paramount importance in enhancing the organization and quality of healthcare at all levels.